Characteristics of Patients with Craniopharyngioma and LongTerm Outcomes of Treatment - Hülya Hacişahinoğulları; Gamze Bilik Oyman; Duygu Dölen; Menekşe Bilge Bilgiç; Rasim Meral; Gülşah Yenidünya Yalın; Nurdan Gül; Ayşe Kubat Üzüm; Özlem Soyluk Selçukbiricik (The Turkish Journal of Ear Nose and Throat)
Objective: Craniopharyngioma (CP) is benign, but its treatment is challenging because of its occurrence in a critical area. Hypothalamic-pituitary dysfunction (HPD) is an important complication that is related to tumour itself or to therapy. This study identified the long-term outcomes of CPs. Material and Methods: Records of 44 patients with CPs followed up at the Istanbul Faculty of Medicine were retrospectively reviewed. Results: The mean age of 34 patients (M/F: 19/15) at diagnosis was 24±13.3 years. The most common symptoms were headache (60.3%) and visual impairment (45.5%). The tumour was localised in suprasellar region in 76.6%, in sellar-suprasellar in 16.7%, and in the sellar region in 6.7% of the patients. The mean tumour diameter was 32.7±10.4 mm (n: 19). Surgery was the first line of treatment in all patients except one, and 13 patients underwent more than one operation. Ten patients received radiotherapy. The median duration of follow-up was 6.5 years. Anterior pituitary dysfunction was observed in all patients: hypocortisolism in 88.2%, hypothyroidism in 97%, hypogonadism in 88.2%, growth hormone deficiency in 68.2%, and prolactin deficiency in 20.6% of the patients. Diabetes insipidus occurred in 97% of the patients. Recurrence developed in 2 patients (after 5-6 years). At the end of all treatments, 15 patients had residual disease. Conclusion: The curative treatment of CP is surgery. HPD is associated with increased mortality and morbidity and decreased quality of life. It is essential to protect the hipothalamo-pituitary axis and to choose the best treatment option for each patient.